Significance of constitutional prescription with special emphasis on temperament through A retrospective study of randomly selected chronic case - Meghaben H. Parmar; Sat Pal Madan; Archana Sharma (Revista Electronica de Veterinaria, 2024)
The ancient Hippocratic temperaments if understood from the modern view point would validate the concept of temperament. An understanding of the drugs in Materia Medica according to modern viewpoint on temperament will make the application of the drugs easy in practice. The susceptibility is modified by constitution and temperament and hence its understanding helps appropriate selection of potency as well. But it should be remembered that it is one of the criteria for the overall assessment of susceptibility and selection of potency. The physician depending upon his judgments of the strengths and weaknesses of every individual temperament can give proper guidelines. A clear understanding of the mental disposition helps not only in the prescribing but also in management of the case as effective counseling differs for every individual personality which is unique.